2023
DOI: 10.3892/ijmm.2023.5236
|View full text |Cite
|
Sign up to set email alerts
|

Smooth muscle cells, interstitial cells and neurons in the gallbladder (GB): Functional syncytium of electrical rhythmicity and GB motility (Review)

Abstract: The motility of the gallbladder (GB) involves the storage, concentration and delivery of bile. GB motor functions are controlled by multiple complex factors, such as extrinsic and intrinsic innervation, humoral factors and neuropeptides. GB emptying results from coordinated contractions of the muscular layers of the GB wall. Depolarization of GB smooth muscle (GBSM) depends on the activation of the regular depolarization-repolarization potential, referred to as slow waves (SWs). These rhythmic SWs of GBSM cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 228 publications
(232 reference statements)
0
3
0
Order By: Relevance
“…TCs are characterized by their small cell body, typically measuring between 9 and 15 µm, and possess one to five extremely long and slender telopodes (Tps). Telopodes consist of alternating segments known as podomers (~80 nm) and podoms (250-300 nm) and are interconnected through homo-and heterocellular junctions, forming intricate three-dimensional networks [54]. Previous research has revealed a significant decrease in the density of c-Kit positive TCs in the gallbladder wall among patients with cholelithiasis.…”
Section: Novel Aspects Regarding the Involvement Of Telocytes In Gall...mentioning
confidence: 99%
“…TCs are characterized by their small cell body, typically measuring between 9 and 15 µm, and possess one to five extremely long and slender telopodes (Tps). Telopodes consist of alternating segments known as podomers (~80 nm) and podoms (250-300 nm) and are interconnected through homo-and heterocellular junctions, forming intricate three-dimensional networks [54]. Previous research has revealed a significant decrease in the density of c-Kit positive TCs in the gallbladder wall among patients with cholelithiasis.…”
Section: Novel Aspects Regarding the Involvement Of Telocytes In Gall...mentioning
confidence: 99%
“…For example, in guinea pigs with cholesterol cholelithiasis, the density and ultrastructure of ICCs in the gallbladder are altered (Huang et al, 2021). Chronic inflammatory response of the gallbladder also leads to ultrastructural damage of the ICCs which in turn affects the normal physiological function of the gallbladder smooth muscle, resulting in abnormal gallbladder activity (Zhang et al, 2022;Ding et al, 2023).…”
Section: Altered Biliary Tract Dynamics and The Formation Of Gallstonesmentioning
confidence: 99%
“…TCs are widespread in a variety of tissues and organs, such as cardiac tissues, [5,6] vessels, [7] the trachea and lungs, [8,9] gallbladder, [10] liver, [11] Intestinal tissues, [12] duodenum, [13] colon, [14] and spleen, [15] and they are also found in the male genitals including the testis, [16] and epididymis, [17] as well as the female genital organs and the uterus, [18,19] oviduct, [20] and placenta. [21] In addition, TCs are also found in the pleura, [22] skin, [1] parotid glands, [23] skeletal muscle, [24,25] and epithelium.…”
Section: Origin and Physiological Role Of Telocytesmentioning
confidence: 99%